Antibacterial and biofilm inhibition activity of biofabricated silver nanoparticles against Xanthomonas oryzae pv. oryzae causing blight disease of rice instigates disease suppression - Mishra, Sandhya (2020)
Antimicrobial activity of silver nanoparticles (AgNPs) has been well documented in earlier studies. As their efficient role in combating phytopathogens has begun recently, there is a huge scope to explore their effectiveness in agriculture. Considering the strong antifungal activity of biosynthesized AgNPs (as reported in our previous study), our main aim is to elucidate their antibacterial activity against bacterial plant pathogens to authenticate their wide range of agricultural applications. The present manuscript highlights the potential role of biosynthesized AgNPs against Xanthomonas oryzae pv. oryzae (Xoo) causing disastrous sheath blight disease of rice worldwide. We observed strong antibacterial activity of biosynthesized AgNPs (size similar to 12 nm) against Xoo at 20, 30 and 50 mu g/mL concentrations. The significant inhibitory impact of AgNPs on biofilm formation by Xoo was noted even at the lower dose of 5 mu g/mL (p = 0.001). Maximum biofilm inhibition (p = 0.000) was caused at 50 mu g/mL concentration of AgNPs in comparison to control. Furthermore, disease suppression by biosynthesized AgNPs was authenticated under greenhouse conditions. Foliar spray of AgNPs significantly reduced the blight symptoms in rice sheaths as shown by 9.25% DLA (% Diseased leaf area) as compared to 33.91% DLA in Xoo inoculated rice plants. Altogether, our data suggest that biosynthesized AgNPs based nanoformulation can be applied for successful management of blight disease of rice. In addition, the antibiofilm strategies instigated by AgNPs can be exploited against a wide range of bacterial phytopathogens. In light of rapidly emerging antibiotic-resistant microbial strains, the current work provides an alternate effective platform for the application of nanoformulation for augmenting sustainability in the agriculture.